Stalker (1979) de Andrei Tarkovsky. A procura do espaço idealizado - Miguel Ezcurdia Royo (2017)
The movie Stalker (1979), from Russian director Andrei Tarkovksy, appears as a respite between two artistic fields whose separation is merely illusory, and marks the culmination of an academic formation always associate with parallel urges, with divergent concerns that find here the possibility to converge in a common ground. The object in study, dissociated in the beginning from the inner problematics of architecture, and centered in the surface on questions that seems to recall that separation - the sci-fi gender, the strong authorship of Tarkovsky's work or the incomprehension raised around his work due to those same authorship choices - progressively revealed the possibility to construct a self-discovery grounded on theoretical assumptions. This way it was possible to drew, during the search for this idealized but dodgy spatiality, the evidence of the methodological and conceptual openness of architectural study, and the confluence of transversal themes that can be found anywhere, when the search is based on the true permeability of a discipline without defined limits. We could say that everything is architecture, that the city, the path, the house and the spaces are universal circumstances to which no discipline can evade, and that the origin of their symbols can't be associated to any concrete discipline, founding that way an interdisciplinary research whose nature denies discipline itself and "appears to us as it is, infinite". Therefore, to study a movie is also to investigate architecture, loaded, this time, with the components of fiction, that allows a reciprocity of unique information only possible due to this interdisciplinarity. As Távora said about the architect: "his fields of activity are multiple - because multiples are the facets of organized space". Stalker (1979) is also, and because of it, about architecture, an architecture gifted by a strong authorship weight that fades at the same time because, ultimately, we are talking about a Russian director - Tarkovksy